The National SOM Survey 2003 - SOM Institute, University of Gothenburg (University of Gothenburg, 2005)
Since 1986 the SOM-institute has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the eighteenth survey in this series. The SOM-institute is a collaboration between three departments at Göteborg University: the Institute for Journalism and Mass Communication, the Department of Political Science, and the School of Public Administration. Since 1998 the survey includes two nation representative samples and uses two different mail questionnaires. One of the questionnaires mainly deals with questions on politics, economy and working life, while the other mainly deals with media, culture and health. One third of the questions asked in the two questionnaires are common for both samples, for example questions about media habits, political attitudes, leisure activities, and social background.
The questionnaire on politics include twelve different subject fields: news; politics and society; Sweden and the surrounding world; mass media, the internet, and possession of technical equipment; society, public service and democracy; consumption and society; knowledge and society; environment and energy; industry and work; activities and interests; work life; and background questions. The media questionnaire is divided into ten subject fields: news and daily papers; politics and society; radio and television; possession of technical equipment, the internet and other media; books, periodicals, and libraries; 'Your view on the morning paper and other media'; activities and interests; work life; background questions; and 'Your yesterday'.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den artonde undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

Riks-SOM 2003 genomfördes som två undersökningar med två representativa urval och två olika formulär, där datainsamlingarna genomfördes parallellt och under identiska förhållanden. Frågeformulären skiljer sig något åt i det att tyngdpunkten i det ena formuläret ligger på politik och samhälle, medan det andra har en tonvikt på frågor om medier, kultur och livsstil. Ungefär en fjärdedel av frågorna är gemensamma för de båda frågeformulären och kan därmed analyseras med dubbla urvalsstorleken som grund.

Politikformuläret innehåller tolv olika frågeområden: nyheter; politik och samhälle; Sveriges förhållande till omvärlden; massmedier, internet och teknikinnehav; samhälle, service och demokrati; konsumtion och samhälle; kunskap och samhälle; miljö och energi; industri och arbete; aktiviteter och intressen; arbetsliv; samt bakgrund. Medieformuläret tar upp tio olika frågeområden: nyheter och dagstidningar; politik och samhälle; radio och TV; teknikinnehav, internet och andra medier; böcker, tidskrifter och bibliotek; 'Din syn på morgontidningen och andra medier'; aktiviteter och intressen; arbetsliv; bakgrund; samt 'Din gårdag'.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 2003
Riks-SOM 2003
Keywords: mass media; massmedia; population migration; migration; energy; energi; environment; miljö; mass media exposure; massmediaexponering; health; hälsa; trust; förtroende; immigrants; invandrare; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; nuclear energy; kärnkraft; membership; medlemskap; party identification; partiidentifikation; trade union membership; medlemskap i fackförening; public services; offentlig service; radio news; radionyheter; television news; tv-nyheter; political allegiance; politisk anhängare; labour and employment; arbete och sysselsättning; educational background; utbildningsbakgrund; political participation; politiskt deltagande; television viewing; tv-tittande; research; forskning; internal politics; inrikespolitik; political parties; politiska partier; internet use; internetanvändning; european economic and monetary union; europeiska ekonomiska och monetära unionen; political leaders; politiska ledare; attitude change; attitydförändring; households; hushåll; clubs; föreningar; libraries; bibliotek; leisure time activities; fritidsaktiviteter; mass media use; mediaanvändning; renewable energy; förnybar energi; trust in government; förtroende för regeringen; radio listening; radiolyssnande; reading (activity); läsande; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap